Civil Society: Pembangun dan Sekaligus Perusak Demokrasi - Bob Sugeng Hadiwinata (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Disillusions with the limits of parliamentary politics and the increasingly dilapidated processes of party politics have generated a renewed interest on civil society as a means of rejuvenating public life. In light of mounting animosity against the